Urban Agriculture as a Social Strategy in Achieving Food Security: Case Study of Yogyakarta City - Amandita 'Ainur Rohmah; Falik Wardana; A. Riyan Rahman Hakiki; Sidharta Adyatma (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
Urbanization and population growth pose significant challenges for the City of Yogyakarta in meeting its food needs and ensuring availability. The rapid development rate that eliminates agricultural land is one of the problems faced by the City of Yogyakarta. On the other hand, the concept of urban agriculture has become a trend that is of interest to the Community and government, especially for dense populations with limited land. Urban agriculture itself has a significant role in achieving sustainable development. This article aims to identify the role and contribution of urban agriculture in the City of Yogyakarta and analyze the innovations and social strategies carried out in achieving food stability in the City of Yogyakarta. The research method employed is a qualitative approach, incorporating a literature review that draws on international journals, national journals, books, and articles from previous researchers. The results of the literature review indicate the successful implementation of urban agriculture in the City of Yogyakarta through two flagship programs, namely Kampung Sayur and Lele Cendol, which can be optimized by the synergy of stakeholders Gandeng Gendong Aktor 5K (Village, Campus, Community, Corporation, and Pemkot). Furthermore, the existence of various community innovations allows the City of Yogyakarta to implement the development of an integrated urban farming system.